THE EPIDEMIOLOGY OF BULIMIA NERVOSA - 2 COMMUNITY STUDIES - Fairburn, C; Cooper, P (1983)
Recent studies of American college students suggest that the syndrome bulimia is common and that individual elements of the condition are even more widespread. In Britain, two community-based studies of the related syndrome bulimia nervosa have been reported. In the first, 499 women who fulfilled diagnostic criteria for bulimia nervosa were identified with the help of a women's magazine. These women closely resembled bulimia nervosa patients attending psychiatric hospitals. Although more than half reported that they wanted medical help, less than one-third had discussed their eating difficulties with a doctor and only 2.5% were currently receiving treatment. The second study investigated the eating habits and attitudes of 369 attenders at a family planning clinic. Of these, 20.9% reported current episodes of 'binge-eating', 2.9% currently used vomiting as a means of weight control; and 1.9% fulfilled diagnostic criteria for bulimia nervosa. Comparison of the two samples indicates that people with bulimia nervosa are prone to have been both overweight and underweight in the past. They also have more disturbed attitudes toward food, eating, body weight, and body shape and a considerably higher degree of psychological disturbance. These studies suggest that bulimia nervosa constitutes a significant undetected source of psychiatric morbidity. The service implications of these findings have yet to be examined.